2019
DOI: 10.15835/nbha47411687
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Iso-α and β Hop Acids Against Pediococcus pentosaceus

Abstract: The goal of the research was to assess the inhibitory effects of  hop extracts, iso-α and β acids, against Pediococcus pentosaceus bacteria, during a short incubation period, both in liquid selective media (high pH values) and beer wort fermentation (low pH values) and testing if the identified iso-α acid stress changes the activity of S. cerevisiae boulardii yeast and ethanol production. Flow cytometry analysis was used for bacterial and yeast cell viability. In relation to the antibacterial activity of β-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The dissociated forms of iso-alpha acids have greater antimicrobial activity, and different pH levels seen in wort fermentation have variable effects on the bactericidal or bacteriostatic activity of those iso-alpha acids. This mostly depends on hop concentration and duration within the wort (Delia et. al., 2019).…”
Section: Resistance Mechanisms To Hop Bitter Acidsmentioning
confidence: 99%
“…The dissociated forms of iso-alpha acids have greater antimicrobial activity, and different pH levels seen in wort fermentation have variable effects on the bactericidal or bacteriostatic activity of those iso-alpha acids. This mostly depends on hop concentration and duration within the wort (Delia et. al., 2019).…”
Section: Resistance Mechanisms To Hop Bitter Acidsmentioning
confidence: 99%
“…Behr and Vogel (2010) proposed two different mechanisms of hop bacterial inhibition: proton-ionophore-induced and oxidative-stressinduced mechanisms [124]. Michiu et al (2019) evaluated the inhibitory effects of hop iso-α and -β acids against the bacterium Pediococcus pentosaceus at both high (6.0-7.0) and low (4.0-5.0) pH values, testing whether the identified iso-α acid stress altered S. cerevisiae boulardii yeast activity and ethanol production [10]. Results pointed out an inhibitory effect of both iso-α and β-acids against P. pentosaceus at the pH values tested, opening the possibility of hops being used as a supplement to prevent beverage contamination with spoilage microorganisms.…”
Section: Antimicrobial and Antiviral Activitymentioning
confidence: 99%
“…Both iso‐α and β‐acids showed reliable inhibitory effects at pH 6.0–7.0 and pH 4.0–5.0 against Pediococcus pentosaceus (Michiu et al, 2019).…”
Section: The Inhibition Effects On Other Microorganismsmentioning
confidence: 99%
“…cerevisiae boulardii yeast, the results showed that iso‐α‐acids do not change the S . cerevisiae activity but prevents the culture from being contaminated by Pediococcus pentosaceus (Michiu et al, 2019).…”
Section: The Inhibition Effects On Saccharomyces Cerevisiaementioning
confidence: 99%